Adoption of innovation : balancing internal and external stakeholders in the marketing of innovation - Brem, Alexander; Viardot, Éric (Springer International Publishing Imprint: Springer, 2015)
This edited volume brings together academics from both innovation and marketing fields to explore the additional value for companies that can be generated with the innovations in marketing and the marketing of innovations. If ideas need to reach the marketplace, then marketing strategies, concepts and tools - such as the continuous development of new product and services - become vital for their success. On the other hand, marketing management is influenced by innovation as illustrated by the way social media and Internet have revolutionized the traditional marketing-mix. Such linkages between innovation and marketing research need to be much stronger as companies have to convince internal and external stakeholders to achieve successful innovation strategies. State-of-the-art research output from different perspectives would suit the needs of a researcher as well as the company CEO alike.